Nano- and micro-sized carnauba wax emulsions-based coatings incorporated with ginger essential oil and hydroxypropyl methylcellulose on papaya: Preservation of quality and delay of post-harvest fruit decay - Miranda, Marcela [UNESP] (2022)
Carnauba wax nano and micro-sized emulsions and hydroxypropyl methylcellulose coatings, alone or combined with ginger essential oils (GEO) were applied on papayas and evaluated under several storage conditions. In a first experiment, storage parameters were: 6 days at 22 °C, and 9 days at 13 °C followed by 5 days at 22 °C. In a second experiment, storage was: 5 days at 22 °C, and 10 days at 16 °C followed by 3 days at 22 °C. Coating effects were dependent on storage conditions. While fruits were in cold storage, there were few changes; however, at 22 °C, the differences between coatings became more evident. Nanoemulsions maintained papaya quality during storage by retarding firmness loss, color changes, and reducing respiration rates, resulting in delayed ripening. GEO exhibited some positive effect on fungal disease control. Nanoemulsion-based coatings improved shelf life by reducing weight loss, color development, and slowing ripening of papaya fruit.